Surface wave characteristic of falling film in swing absorber and its influences on absorption performance. (25th January 2018) - Gao, Hongtao; He, Mingyue; Sun, Weiting; Yan, Yuying
Highlights: A CFD model considered the momentum and the phase transfer mass source term. The numerical results reveal five different regions in the surface wave evolution. Experimental results show that three parameters have great impacts on surface wave. A proper swing movement improves the heat and mass transfer in absorber. Abstract: Falling film is widely used in absorption refrigeration absorber. In this paper, a model of simultaneous heat and mass transfer process in absorption of refrigerant vapor into solution is developed to investigate the evolution process of surface wave on falling film in swing absorber. Surface wave patterns in a wide range of swing angle (0°–10°) have been obtained as the swing period is 4 s. The numerical results reveal that the surface wave evolution of liquid film includes five different regions. Experiments are conducted focusing on effects of swing movement on variation of surface wave of falling film in swing absorber and the influences on the heat and mass transfer of film. Experimental results show that three parameters including flow rate, swing amplitude and swing period have great impacts on variation of surface wave of falling film, and thus affect the heat and mass transfer performance. A proper swing movement (e.g. swing amplitude is not greater than 10° when swing period is 8 s) will improve the heat and mass transfer in absorber, but the excessive swing movement (e.g. swing amplitude is greater than 15° when swing period is 8 s, or swing period is shorter than 4 s when swing amplitude is 10°) will have the opposite effect.